A critical evaluation of 3D spatial information models for managing legal arrangements of multi-owned developments in Victoria, Australia. Issue 10 (3rd October 2018) - Rajabifard, Abbas; Atazadeh, Behnam; Kalantari, Mohsen
ABSTRACT: Three-dimensional (3D) spatial information models are increasingly being adopted to help communicate the spatial dimensions of complex built environments. Land administration practices in multi-owned developments include the subdivision, registration and management of legal interests associated with private, communal and public properties, which are often located along the vertical dimension. The spatial structure of each legal interest is normally composed of invisible spaces, defined as the inside and outside of multi-owned developments, as well as physically built structures. Additionally, a wide variety of legal boundary types mark out the spatial limits of the individual parts of each legal interest. These legal boundaries are typically delineated by either relying on fixed surveying measurements or referencing physically existent objects. This article provides a critical assessment of 3D spatial information models in terms of their capabilities for modelling legal interests and legal boundaries defined in the Victorian jurisdiction. We classify these models into three categories: purely legal, purely physical and integrated. This assessment provides the basis for developing a new 3D spatial information model, which would subsequently support a pathway towards realising the Victorian land administration system in a 3D digital environment.